Accelerated CO2 mineralization and utilization for selective battery metals recovery from olivine and laterites. (20th March 2023) - Wang, Fei; Dreisinger, David; Xiao, Yuchang
Abstract: The reduction of CO2 emissions through both carbon capture utilization and storage and clean energy transition is accelerating all over the world. However, the global supply of required battery metals for clean energy transition is in deficit and the effective CO2 mineralization for permanent CO2 storage is still in challenge. It has been found in this study that CO2 mineralization can be significantly accelerated by complexation reaction and can be utilized simultaneously to recover critical battery metals. An integrated process of CO2 mineralization and synergistic battery metal recovery has been developed and is robust for various feed materials including nickel-barren olivine and all-types of nickel-rich laterites. In this novel approach, CO2 is a reagent used to convert basic silicate minerals to stable mineral carbonates and in return critical battery metals can be selectively recovered. Each tonne CO2 sequestered can be used to recover 98.7 kg nickel and 2.7 kg cobalt with over 90% nickel and cobalt recovery and around 60% CO2 mineralization efficiency. The process utilizes the strong competition between carbonate precipitation and complexation formation during the simultaneous metal extraction and enhanced CO2 mineralization. This work can make significant contributions to the clean energy transition with enhanced supply of critical battery metals and to CO2 emission reduction with enhanced CO2 storage and utilization. Graphical abstract: Image 1 Highlights: Mechanism of CO2 mineralization is updated and can be utilized for hydrometallurgy. Accelerated CO2 mineralization of olivine is through complexation reaction. Accelerated CO2 mineralization for simultaneous recovery of critical battery metals. Strong competition between carbonation and complexation is key for the acceleration. Strong competition between carbonation and complexation for high leaching selectivity.